Meningkatkan Niat Menggunakan Dompet Digital pada Generasi Z dan Milenial dengan Cashback promotion sebagai Mediator - Debi Eka Putri; Onita Sari Sinaga; Edy Dharma; Julyanthry Julyanthry; Acai Sudirman (Jurnal Ilmu Manajemen, 2022)
The main objective of this research is to analyze the effect of cashback promotion as a mediator on the influence of perceived ease of use, perceived usefulness, social influence, trust, and security on the interest in using digital wallets in generation Z and millennial generations. The research method includes library research design and field research with a quantitative approach. The research subjects taken in this study were Generation Z and the Millennial Generation of Culinary SMES in Pematangsiantar City. Data collection techniques using observation, interviews, questionnaires, and documentation. The data analysis method used is Partial Least Square (PLS) with Smartpls statistical software. The study stated positive and significant results between perceived benefits and the social influence of cashback promotions. Furthermore, positive and significant results are perceived ease of use, perceived benefits, trust, and cashback promotions. The results also show that the safety factor has a negative and insignificant effect on the intention to use. For the mediating relationship, it can be concluded that cashback promotion succeeds in mediating the relationship between perceived benefits and social influence on intention to use. The results of this study indicate that the average Generation Z and Millennials have low literacy of digital wallet security issues. Socialization or literacy activities are needed regarding information security which the fintech industry or digital wallet developers routinely carry out.